APPLICATION OF ACTIVE LEARNING METHODS IN IMPROVING STUDENT LEARNING ACTIVITIES IN SUBJECTS ISLAMIC EDUCATION - Riamah (Journal of Quality Islamic Education Research, 2025)
Islamic religious education (PAI) plays an important role in learning in public schools and madrasahs. The purpose of this study is to explore the implementation of active learning approaches in PAI, and its impact on student engagement and understanding. The method used in this study is library research, data collection is carried out by searching, collecting, and reconstructing information from various relevant sources, such as books, scientific journals, and previously published research results, which specifically examine various active learning methods such as role playing, experiential learning, and question and answer dialogues. The results of the study indicate that the implementation of active learning can increase student participation, conceptual understanding, and their social attitudes. Although there are challenges in implementation, such as differences in student abilities and teacher readiness, this approach has succeeded in creating a dynamic and interactive learning environment. Active learning in PAI does not only focus on the transfer of knowledge, but also on the development of critical thinking skills and the application of religious values ​​in everyday life.